Primary cesarean section in Sub-Saharan Africa: A systematic review and meta-analysis using the Robson Ten-Group Classification System - Kindu Yinges Wondie; Endalk Birrie Wondifraw; Miteku Andualem Limenih; Berihun Agegn Mengistie; Getie Mihret Aragaw; Nuhamin Tesfa Tsega; Zelalem Nigussie Azene (PLoS ONE, 2026)
Background The overuse of cesarean sections, mainly of primary procedures, is a major contributor to perinatal mortality in Sub-Saharan Africa. The Robson Ten-Group Classification System is the global standard for cesarean section rate. Evidence on the pooled primary cesarean section rate using this system in Sub-Saharan Africa SSA remains limited. Materials and methods A systematic review and meta-analysis were conducted. PubMed, Scopus, ScienceDirect, Google Scholar, Google, and ResearchGate were searched for studies published between 2001 and February 22, 2025. Data were extracted into Microsoft Excel and analyzed using Stata 17. A random-effects model was applied to calculate the pooled rate. Study quality was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data. Publication bias was assessed using a Doi plot and the Luis Furuya-Kanamori index. Heterogeneity was assessed using the I² statistic. Results The pooled facility‑based primary cesarean section rate, derived from 25 institution‑based studies (213,117 births; predominantly secondary and tertiary hospitals), in Sub-Saharan Africa was 18.7% (95% CI: 16.2–21.4; 95% prediction interval: 8.4%−36.8%). Robson Groups 1 and 2 were the largest contributors (47.5%), with Group 1 alone accounting for 37.1%. In both nulliparous and multiparous women, primary cesarean section was more common after spontaneous labor than after induction or elective procedures. Significant heterogeneity was observed across studies (I² = 99.64%, p < 0.001). No evidence of publication bias was found (LFK index = −0.27). Conclusion The facility‑based primary cesarean section rate in Sub-Saharan Africa exceeded the WHO global reference, with Robson Groups 1 and 2 being the largest contributors. High rates of prelabor cesarean and elevated rates following spontaneous labor raise concern for possible overuse, but unmeasured comorbidities and referral bias cannot be excluded. Stricter adherence to evidence-based protocols, routine use of the Robson classification for clinical audits, and linkage with indication‑level data are essential for improving obstetric care.